Effects of Four-Week Supplementation with a Multi-Vitamin/Mineral Preparation on Mood and Blood Biomarkers in Young Adults: A Randomised, Double-Blind, Placebo-Controlled Trial - White, David J. (Nutrients, 2015)
This study explored the effects of four-week multi-vitamin and mineral (MVM) supplementation on mood and neurocognitive function in healthy, young adults. Fifty-eight healthy adults, 18–40 years of age (M = 25.82 years, SD = 4.87) participated in this randomised, double-blind, placebo-controlled trial, in which mood and blood biomarkers were assessed at baseline and after four weeks of supplementation. Compared to placebo, MVM supplementation was associated with significantly lowered homocysteine and increased blood B-vitamin levels (p < 0.01). MVM treatment was also associated with significantly improved mood, as measured by reduced scores on the “depression-dejection” subscale of the Profile of Mood States (p = 0.018). These findings suggest that the four weeks of MVM supplementation may have beneficial effects on mood, underpinned by elevated B-vitamins and lowered homocysteine in healthy young adults.